Visita aos depósitos de Alvarães (Viana do Castelo, Portugal) - Alves, M. I. Caetano (1997)
This paper describes the main sedimentary composition and the sedimentation model of Alvarães deposits (Viana do Castelo, NW Portugal), formed during Late Pliocene to Early Pleistocene.